Men's perceptions on educational intervention participation at workplace - Gabriela Schiavon Ganassin; Guilherme Oliveira de Arruda; Mayckel da Silva Barreto; Magda Lúcia Felix de Oliveira; Sonia Silva Marcon
ABSTRACT Objective: todescribe the application of educational intervention performed with working men and identify, according to their perceptions, the main results obtained. Methods: a descriptive and exploratory research, of qualitative nature, developed in a municipality of Southern Brazil, with 35 metallurgists. Data were collected between March and June 2014, through the recording of the operating groups and participant observation. Transcripts and field diaries were submitted to content analysis. Results: participants intensified their interest in the search for health information, and some of them managed to implement changes in lifestyles, especially in relation to eating habits and sedentarism, and the support of the group was perceived as motivating for the changes. Final considerations: health education activities that embrace meaningful themes for participants and are built by a cohesive group whose members support each other, favor lifestyle modification.